2022
DOI: 10.1177/21582440221102424
|View full text |Cite
|
Sign up to set email alerts
|

The Concept of Wealth (māl) in the Sharīʿah and Its Relation to Digital Assets

Abstract: The study aims to address the concept of wealth from the perspective of the Sharīʿah and its relationship to contemporary digital assets such as cryptocurrency (Bitcoin). The qualitative research approach is adopted for this research. The data is collected from several resources such as books, journal articles, reports, conferences papers, and websites. The data is analyzed through an explanatory research approach by providing scholars’ opinions and their arguments on the subject matter. The findings of this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Contemporarily, the Jumhur jurists' definition of something as a valuable asset accommodates material and immaterial objects in the form of benefits in a more accommodative manner than the Hanafiyah view (Rosele et al, 2022). As we see that currently the development of assets that can be guaranteed or can become marhūn are not exclusively limited to objects that are physical in nature, but also that are immaterial in nature.…”
Section: Can Be Handed Overmentioning
confidence: 83%
“…Contemporarily, the Jumhur jurists' definition of something as a valuable asset accommodates material and immaterial objects in the form of benefits in a more accommodative manner than the Hanafiyah view (Rosele et al, 2022). As we see that currently the development of assets that can be guaranteed or can become marhūn are not exclusively limited to objects that are physical in nature, but also that are immaterial in nature.…”
Section: Can Be Handed Overmentioning
confidence: 83%
“…In contrary, Classic Hanafi jurists disregard inheritability of intangible asset (Islam, 1999). Thus, Bitcoin should fall within the definition and attributes of mal as mentioned above for it to be considered as mal (Rosele et al, 2022) before it can be inherited. Rosele et al (2022) also found that bitcoin meets fulfil all essential features or attributes of mal set by classical and contemporary jurists.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, Bitcoin should fall within the definition and attributes of mal as mentioned above for it to be considered as mal (Rosele et al, 2022) before it can be inherited. Rosele et al (2022) also found that bitcoin meets fulfil all essential features or attributes of mal set by classical and contemporary jurists. Where it has its financial value according to the digital community that uses it where its capital market is USD $319,450,492,443 as at end of December 2022(CoinMarketCap, 2022.…”
Section: Resultsmentioning
confidence: 99%
“…Polas et al (2020) argue that, virtual currency is a form of money and fulfils money related issues (mode of exchange, unit of record, and store of noteworthy worth). It is therefore, one of the types of currencies that emerged as a result of the process of creating and developing money (Oziev & Yandiev, 2017), transcending from the era of barter, gold, silver coins, and gradually paper money, to a digital form (Rosele et al, 2022). Meanwhile, Oziev & Yandiev (2017) view that, crypto-currency, particularly Bitcoin and its likes, for saving purposes, investment and accumulation are impermissible under the Sharī'ah.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ahmed Kamel Midin Meera, the former dean of the Institute of Islamic Banking and Finance at the International Islamic University of Malaysia, however, adds that: "in order for digital currency to be accepted in the Islamic financial industry, it must have a measure of value, which has to be a monetary commodity (Oziev & Yandiev, 2017). Rosele et al (2022)conclude that, crypto-currency falls under the category of mutaqawwim (Islamically recognised value), as long as it does not contravene the Sharī'ah guidelines of māl (wealth).…”
Section: Literature Reviewmentioning
confidence: 99%